2018
DOI: 10.21926/obm.genet.1803036
|View full text |Cite
|
Sign up to set email alerts
|

Histone O-GlcNAcylation and Potential Biological Functions

Abstract: Histone modifications play an important role in the control of DNA-based processes by altering the structure and function of chromatin. O-linked N-acetylglucosamine (O-GlcNAc) modification is a form of post-translational modification of proteins that affects the serine (Ser)/threonine (Thr) residues. This process is controlled by a single pair of enzymes, i.e. O-GlcNAc transferase (OGT) and O-GlcNAcase (OGA). Recent evidence indicates the existence of O-GlcNAc modification of histones, with 16 histone O-GlcNAc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 89 publications
(130 reference statements)
0
3
0
Order By: Relevance
“…These findings are consistent with the effect and direction of the genetic interactions we observed between OGT and PRC2.1 and OGT and ERK, the direction of ‘information flow’ within the cell ( Figure 7E ), and the effects of our genetic manipulations. OGT could also affect chromatin accessibility by GlcNAcylating histones, although the function and effects of these histone modifications are still poorly understood (Gambetta and Müller, 2015; Hirosawa et al, 2018 ; Konzman et al, 2020 ; Olivier-Van Stichelen et al, 2017 ). Another outstanding question is how OGT is targeted to chromatin and whether this recruitment is dynamic and related to nutrient availability.…”
Section: Discussionmentioning
confidence: 99%
“…These findings are consistent with the effect and direction of the genetic interactions we observed between OGT and PRC2.1 and OGT and ERK, the direction of ‘information flow’ within the cell ( Figure 7E ), and the effects of our genetic manipulations. OGT could also affect chromatin accessibility by GlcNAcylating histones, although the function and effects of these histone modifications are still poorly understood (Gambetta and Müller, 2015; Hirosawa et al, 2018 ; Konzman et al, 2020 ; Olivier-Van Stichelen et al, 2017 ). Another outstanding question is how OGT is targeted to chromatin and whether this recruitment is dynamic and related to nutrient availability.…”
Section: Discussionmentioning
confidence: 99%
“…Although we did not measure cell-specific changes in H3K27me3 (which is not technically feasible), our experiments showing that inhibiting the complex’s catalytic activity prevents OGT-mediated taste plasticity, suggest that H3K27me3 is the silencing signal. However, OGT could also affect chromatin accessibility by GlcNAcylating histones, although the function and effects of these histone modifications are still poorly understood 41,70,101,102 . Our data also showed that OGT catalytic activity is required for chromatin accessibility and gene repression, suggesting that OGT may affect PRC2.…”
Section: Discussionmentioning
confidence: 99%
“…6E), and the effects of our genetic manipulations. OGT could also affect chromatin accessibility by GlcNAcylating histones, although the function and effects of these histone modifications are still poorly understood (Gambetta and Müller, 2015; Hirosawa et al, 2018; Konzman et al, 2020; Olivier-Van Stichelen et al, 2017). Another outstanding question is how OGT is targeted to chromatin and whether this recruitment is dynamic and related to nutrient availability.…”
Section: Discussionmentioning
confidence: 99%